Baseline renal function and adverse outcomes in pregnancies complicated by pregestational diabetes. (12th December 2022) - Champion, Macie L.; Steele, Robin; Sinkey, Rachel; Tita, Alan T.; Harper, Lorie M.
Abstract: Objective: To examine the relationship between baseline renal function (serum creatinine, urine protein to creatinine ratio) in women with diabetes and adverse pregnancy outcomes. Study Design: This was a retrospective cohort study of singleton pregnancies with pregestational diabetes and baseline renal function tests <20 weeks gestational age (wga) from the years 2007 to 2013. Those with baseline creatinine ≥1.2 mg/dL were excluded due to the association of renal disease with adverse outcomes. The primary outcome was the development of preeclampsia with severe features at <34 wga. Secondary outcomes were preeclampsia at any gestational age, preterm birth, indicated preterm birth, small for gestational age, and a neonatal adverse outcomes composite. The relationship between baseline renal function and the primary outcome was assessed with ROC curves. Objective cutoffs were determined by the Liu method. Outcomes were compared using univariable and multivariable analyses. Results: Baseline renal function was assessed in 321 women with pregestational diabetes. With baseline serum creatinine <1.2 mg/dL serum creatinine was not associated with preeclampsia <34 weeks (AUC 0.47, 95% CI = 0.32–0.63). Urine protein to creatinine (UPC) ratio was moderately associated with preeclampsia <34 weeks with area under curve (AUC) 0.56 (0.39–0.74). Baseline creatinine above the Liu cutoff (0.65 mg/dL) was not significantly associated with primary or secondary outcomes (Table 1). UPC above the Liu cutoff (0.21) was significantly associated with severe preeclampsia <34 wga (24% vs 3.7%, aOR = 6.6, 95% CI = 2.1–20.8), with development of preeclampsia at any gestational age (56% vs 23.4%, aOR = 3.3, 95% CI = 1.4–7.9), and preterm birth (80% vs 36.2%, aOR 6.5 95% CI = 2.3–18.1). Conclusion: Creatinine was not associated with adverse pregnancy outcomes at thresholds <1.2 mg/dL in women with pregestational diabetes. Those with a baseline UPC ≥ 0.21 have an increased risk of preeclampsia and preterm delivery. Baseline 24 hr urine protein should be obtained in these patients to aid in counseling and future diagnosis of preeclampsia. Key Points: Baseline renal function tests are recommended in patients with pregestational diabetes, but values associated with pregnancy risk are poorly defined. This study evaluated the relationship between baseline renal function tests in patients with pregestational diabetes and adverse pregnancy outcomes. We found urine protein to creatinine ratio ≥0.21 to be associated with the development of severe preeclampsia <34 weeks gestational age as well as preeclampsia at any gestational age.